Analisis Scientometrik Tentang Komunikasi dan Dakwah Islam dalam Literatur Ilmiah - Nadia Nurul Izza (Program studi Keagamaan Islam, 2023)
The purpose of this study is to examine research on Islamic communication and da'wah that has been published by Dimensions-indexed journals between 2012 and 2022. The study uses both qualitative and descriptive statistics methods. To analyze the 275 papers, VOSviewer was used to create bibliometric maps, while NVivo 12 Plus and frequency words were employed to evaluate them. The study found that the number of publications on Islamic communication and da'wah varied annually. The cluster analysis revealed that Islamic communication and da'wah research encompassed dawah communication, Islamic dawah media, Islamic broadcasting, and the movement or development of Islamic dawah communication. This research can serve as a starting point for experts to create graphical representations of research trends in Islamic communication and da'wah in published scientific research.